Advanching family theories - White, James M. (Thousand Oaks : Sage, 2005)
Contenido: Family theory and social science. Science and its critics. Theory, models, and metaphors. Function and types of theory. Rational choice and the family. Transition theory. Theory, research, and meta-theory. Theory and human values.